The Relation Between Translation and Ideology as an Instrument for the Establishment of a National Literature - Aksoy, Nüzhet (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
The relation between translation and ideology is an example of a concrete case for a nation’s struggle to take its place in the modern world. In the early years of the Turkish Republic, established by M. Kemal Atatürk and his followers after the Turkish War of Liberation (1919-1923), the dominant state ideology focused on a full-scale enlightenment and development initiative on all levels of society. The conditions which created the Renaissance and the spirit of humanism in the West were taken as a model and translation became one of the main instruments for the establishment of a modern society and a national literature following many reforms in education and language. This paper investigates how the state ideology manipulated translation, and its effects on the emergence of modern Turkish Literature.